Literature Review : In Vitro And In Vivo Study Of Anti-Cancer Activity Of Syzygium Cumini Fruit, Stem Bark, Seeds, Leaves - putri septiyani; aulia rizqi septiani; winda aryani; himyatul hidayah (Peneliti.net, 2023)
Indonesia is a country that has very abundant natural resources (Summa, 2019), one of which is by having various types of plants that have properties for traditional medicine (Adiyasa & Meiyanti, 2021). For this reason, Indonesian people are very interested in traditional medicines because the plant-based ingredients are easy to get, easy to mix, and also very affordable prices (Widaryanto & Azizah, 2018). Jamblang fruit (Syzygium cumini L.) is one of the tropical fruits that can be used as medicine to treat various diseases. Jamblang fruit can be found in Australia, Tropical Asia, and Indonesia. Jamblang or duwet fruit is a plant that belongs to the Myrthacceae family, all parts starting from fruit, leaves, seeds of jamblang fruit can be used as traditional medicine (Katiyar et al., 2016). The jamblang fruit itself has several ingredients in it, including high levels of flavonoids, alkaloids, resins, tannins, and also essential oils so that the jamblang fruit is very beneficial for health. The jamblang seeds contain gallic acid, ellagic acid, corilagen, 3,6-hexahydroxy diphenoylglucose, 1-galloylyglucose, 3galloylyglucose, quercetin, β-sitostero, quercetin kaempferol, myricetin, and genin (Jagetia, 2017). Whereas jamblang leaves themselves contain acylated flavonol glycosides, triterpenoids, tannins, quercetin, myricetin, myricitin, myricetin 3-O-4-acetyl-Lrhamnopyranoside, esterase, and galloyl carboxylase (Kumawat et al., 2018). For this reason, the compounds contained in jamun fruit make jamblang fruit a plant that has properties as antidiabetic, anti-inflammatory, anticancer, antioxidant, hypoallergenic, antiviral, antifungal, antibacterial, and also antipyretic (LPPM Biopharma Study Center, IPB & Gagas Ulung, 2014)